ORNAMENTAL FISH MARKETING AND AQUARIUM EQUIPMENT IN PEKANBARU RIAU PROVINCE - Desi Elpita; Hendrik '; Hamdi Hamid (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Research about marketing of ornamental fish and aquarium supplies are carried out from August to September 2015 in the city of Pekanbaru in Riau province. This study aims to determine the area of origin of ornamental fish, fish species were seeded and problems in marketing of ornamental fish and aquarium. The method used is a survey method to determine the respondents conducted by proportional random sampling. The number of respondents who were taken as many as 10 businesses ornamental fish and aquarium from 8 subdistricts.Results of this study indicate that based on where his life ornamental fish marketed in Pekanbaru from Medan (North Sumatra, Bogor (West Java) and Pekanbaru for freshwater species, while kind of seawater derived from Padang (West Sumatra) and Sidoarjo (Jawa East). Ornamental fish species are seeded based on several criteria are Arowana fish and Goldfish fresh water and fish Nemo for this type of seawater. The obstacles faced by entrepreneurs ornamental fish are fish that is seasonal, non-fulfillment of consumer demand because of unavailability of products.Keywords: Marketing, Ornamental Fish and Aquarium, Pekanbaru